2022
DOI: 10.1136/bmjopen-2022-062124
|View full text |Cite
|
Sign up to set email alerts
|

Global evidence on falls and subsequent social isolation in older adults: a scoping review

Abstract: BackgroundFalls are a leading cause of injury-related hospitalizations among adults aged 65 years and older and may result in social isolation.ObjectiveTo summarise evidence on falls and subsequent social isolation and/or loneliness in older adults through a scoping review.Eligibility criteriaStudies were eligible for inclusion if the population had a mean age of 60 years or older, they examined falls and subsequent social isolation, loneliness, fear of falling or risk factors and were primary studies (eg, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[42][43][44] Furthermore, the consequences associated with falls, such as social isolation and activity limitation due to falls, as well as the fear of falling, may further increase the risk of cognitive decline. [10][11][12][13][14]45 Overall, these ndings highlight the signi cance of falls as a potential risk factor for cognitive decline. They emphasize the importance of implementing targeted interventions and strategies to prevent falls and mitigate cognitive decline in individuals who have experienced falls.…”
Section: Association Between Falls and Cognitive Declinementioning
confidence: 77%
See 1 more Smart Citation
“…[42][43][44] Furthermore, the consequences associated with falls, such as social isolation and activity limitation due to falls, as well as the fear of falling, may further increase the risk of cognitive decline. [10][11][12][13][14]45 Overall, these ndings highlight the signi cance of falls as a potential risk factor for cognitive decline. They emphasize the importance of implementing targeted interventions and strategies to prevent falls and mitigate cognitive decline in individuals who have experienced falls.…”
Section: Association Between Falls and Cognitive Declinementioning
confidence: 77%
“…Additionally, fall-related consequences like forced social isolation, diminished physical activity, and the fear of falling can exacerbate the potential risk of cognitive decline. [10][11][12][13][14] However, previous cohort studies that attempted to associate baseline falls with cognitive decline and incident dementia lacked generalizability due to a small sample size 15 and a limited ethnic representation 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations of these factors are needed to clarify the relationship between osteoporosis and social isolation, because the study reported mental health outcomes related to falls and subsequent social isolation. 12 In conclusion, social isolation with pain in the lower limbs or osteoporosis treatment might be associated with medication counts. Our results are expected to assist in establishing approaches to improvement in social isolation.…”
mentioning
confidence: 92%
“…Falls and fear of falling (FOF) amongst older adults are common issues in countries with rapidly aging populations. Up to one-third of older adults ≥65 years fall each year in Canada and the United States, half of whom may experience recurrent falls, and falls accounts for nine in ten of all fractures in older adults (14,15). FOF on the other hand affects between 20 and 85% of older adults, with significant threat to autonomy and participation (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…FOF on the other hand affects between 20 and 85% of older adults, with significant threat to autonomy and participation (16,17). Both falls and FOF are associated with social isolation, depression, anxiety, poor quality of life, and cognitive impairment, which result in participation restriction that imposes significant burden on the society and healthcare system at large (15,18,19). Risk factors common to both participation restriction, and falls and FOF are older age, low socio-economic status, gender where FOF is more prevalent in females, poor perceived health, frailty, and comorbidities (15,20,21).…”
Section: Introductionmentioning
confidence: 99%